Enhancing BVAG data replication transactions with highpriority-neighbour fault tolerance approach - Sharifah Hafizah, Sy Ahmad Ubaidillah; Noraziah, Ahmad; Herawan, Tutut; Alkazemi, Basem Y.; Ahmad Shukri, Mohd Noor; Noriyani, Mohd Zin (Faculty of Computer Science & Information Technology, University of Malaya, 2025)
In distributed systems with failure interruption, the performance of database replication transactions might become very critical. Any distributed system that enforce data replication can be impacted by this problem. The fault tolerance approach is crucial to ensure the data replication transactions are always effective and dependable despite failures. The key advantage of fault tolerance is its capacity to complete the transaction notwithstanding a failure and restore system availability. This paper proposes a fault tolerance approach namely Binary-VoteAssignment-Grid with High-Priority-Neighbour (BVAGHPN). It improves the efficiency of the data replication transaction in term of total execution time. This approach combines BVAG data replication transaction manager with the HPN to manage the transaction in the event of disasters. Instead of waiting for the problem to be fixed in the event of disaster, BVAGHPN halts the transaction on a failure replica, remove the failing replica from the alive quorum, and proceed the transaction with other replicas based on its own rating. BVAGHPN improves the outcomes of BVAG and BVAGCR in terms of the total execution time for two cases, PR failure and NR failure. For PR failure, BVAGHPN exceeds BVAG with 69.02% and BVAGCR (54.67%), respectively. Meanwhile, for NR failure, BVAGHPN improves BVAG with 76.88% and BVAGCR (71.97%).